2000
DOI: 10.1073/pnas.97.23.12513
|View full text |Cite
|
Sign up to set email alerts
|

Repression of human papillomavirus oncogenes in HeLa cervical carcinoma cells causes the orderly reactivation of dormant tumor suppressor pathways

Abstract: Most cervical carcinomas express high-risk human papillomaviruses (HPVs) E6 and E7 proteins, which neutralize cellular tumor suppressor function. To determine the consequences of removing the E6 and E7 proteins from cervical cancer cells, we infected HeLa cells, a cervical carcinoma cell line that contains HPV18 DNA, with a recombinant virus that expresses the bovine papillomavirus E2 protein. Expression of the E2 protein resulted in rapid repression of HPV E6 and E7 expression, followed Ϸ12 h later by profoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
305
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 403 publications
(323 citation statements)
references
References 47 publications
12
305
0
3
Order By: Relevance
“…HeLa cell line is well known as a cervical cancer cell line with dormant p53 pathway for its infection of human papillomavirus 18 (HPV18), in which the viral protein E6 accelerates p53 degradation by binding to p53 protein [30][31][32]. However, when HeLa cells were treated with an potent anti-tumor reagent Tripchlorolide (TC), it was found that the E6/E7 mRNA was diminished significantly after 12-h treatment and was reduced to an undetectable level after 24-h treatment (Fig.…”
Section: Results P53 Restoration and Activation Of Hela Cells By Tcmentioning
confidence: 99%
“…HeLa cell line is well known as a cervical cancer cell line with dormant p53 pathway for its infection of human papillomavirus 18 (HPV18), in which the viral protein E6 accelerates p53 degradation by binding to p53 protein [30][31][32]. However, when HeLa cells were treated with an potent anti-tumor reagent Tripchlorolide (TC), it was found that the E6/E7 mRNA was diminished significantly after 12-h treatment and was reduced to an undetectable level after 24-h treatment (Fig.…”
Section: Results P53 Restoration and Activation Of Hela Cells By Tcmentioning
confidence: 99%
“…Thus, p130/p107 may be involved in regulating Usp4 shuttling. Of significance in this context is the fact that p130 shuttles between nucleus and cytoplasm, with its nuclear export LMB-insensitive (40) and that the levels of p130 and p107 are also depleted in HeLa and Saos-2 cells (41,42), which show exclusively nuclear Usp4 (Fig. 2).…”
Section: Discussionmentioning
confidence: 99%
“…A clonal association between virus and tumor cell is usually established via viral integration, and continued expression of viral oncogenes is necessary for maintenance of the malignant phenotype. [28][29][30] The absence of viral sequences is therefore strong evidence against a role for these viruses in the etiology of retinoblastoma. These findings therefore contradict previous reports in which HPV genomic DNA was detected in a subset of bilateral (presumed germline RB1 mutation) and unilateral nonfamilial (presumed nonhereditary) retinoblastoma tumors in Mexico and South America.…”
Section: Discussionmentioning
confidence: 99%